2020
DOI: 10.1038/s41467-020-17180-x
|View full text |Cite
|
Sign up to set email alerts
|

An ecological framework to understand the efficacy of fecal microbiota transplantation

Abstract: Human gut microbiota plays critical roles in physiology and disease. Our understanding of ecological principles that govern the dynamics and resilience of this highly complex ecosystem remains rudimentary. This knowledge gap becomes more problematic as new approaches to modifying this ecosystem, such as fecal microbiota transplantation (FMT), are being developed as therapeutic interventions. Here we present an ecological framework to understand the efficacy of FMT in treating conditions associated with a disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 107 publications
1
53
0
Order By: Relevance
“…For the transplantation, the stool is mixed with saline or medium, homogenized and filtrated, and the supernatant is transferred into the patient’s colon by means of a colonoscopy, nasogastric tube or enema. To increase the chance of recovery, the transfer of microorganisms as well as other molecules, e.g., short-chain fatty acids, is required [ 19 , 20 ]. Then, the success of FMT has been shown to result in recovery rates of up to 90% [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the transplantation, the stool is mixed with saline or medium, homogenized and filtrated, and the supernatant is transferred into the patient’s colon by means of a colonoscopy, nasogastric tube or enema. To increase the chance of recovery, the transfer of microorganisms as well as other molecules, e.g., short-chain fatty acids, is required [ 19 , 20 ]. Then, the success of FMT has been shown to result in recovery rates of up to 90% [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, changes in the network structure of the microbiota could have a significant impact on how a host responds to subsequent perturbations such as antibiotic treatment or infection with a pathogen. For example, Xiao et al demonstrated that bacterial microbiota network structure could be used to predict FMT efficacy for treatment of recurrent infection by Clostridioides difficile by comparing the microbiota networks of donors and recipients ( 38 ). In the next set of experiments, we examined whether the differences in microbiota composition and network structure of uncolonized or C. albicans - colonized mice affected the ecological resistance of the bacterial communities.…”
Section: Resultsmentioning
confidence: 99%
“…Heterologous FMT is the most widely used gut microbiome intervention in clinical settings. Most research so far has focused on the efficacy and safety of FMT (Baruch et al, 2021; Davar et al, 2021; Ding et al, 2019; Tabbaa et al, 2018; Xiao et al, 2020). Several studies reported that heterochronic FMT could result in the transfer of some physiological properties from the donor to the recipient, including lifespan and healthspan (Bárcena et al, 2019; Smith et al, 2017), the germinal center reaction (Keeney et al, 2014), and neurogenesis and behavior (D’Amato et al, 2020; Rinninella et al, 2019).…”
Section: Discussionmentioning
confidence: 99%